Ultrasensitive 2D Bi2O2Se phototransistors on silicon substrates - Fu, Qundong (2020)
2D materials are considered as intriguing building blocks for next-generation optoelectronic devices. However, their photoresponse performance still needs to be improved for practical applications. Here, ultrasensitive 2D phototransistors are reported employing chemical vapor deposition (CVD)-grown 2D Bi2 O2 Se transferred onto silicon substrates with a noncorrosive transfer method. The as-transferred Bi2 O2 Se preserves high quality in contrast to the serious quality degradation in hydrofluoric-acid-assisted transfer. The phototransistors show a responsivity of 3.5 × 104 A W-1 , a photoconductive gain of more than 104 , and a time response in the order of sub-millisecond. With back gating of the silicon substrate, the dark current can be reduced to several pA. This yields an ultrahigh sensitivity with a specific detectivity of 9.0 × 1013 Jones, which is one of the highest values among 2D material photodetectors and two orders of magnitude higher than that of other CVD-grown 2D materials. The high performance of the phototransistor shown here together with the developed unique transfer technique are promising for the development of novel 2D-material-based optoelectronic applications as well as integrating with state-of-the-art silicon photonic and electronic technologies.